Exploring the potential of Paris polyphylla var. yunnanensis pollen manipulation in modifying seed dormancy - Wang, Meng; Wang, Qiuxia; Wang, Xiao; Wang, Dingkang; Yin, Xudong; Qiao, Yanwen; Ma, Mingkai; Du, Yanli; Wang, Bin (Frontiers in Plant Science, 2024)
Paris polyphylla var. yunnanensis, a well-known Chinese medicinal herb, shows a unique physiological trait characterized by the cyclic opening and closing of its anthers after pollen maturation. The aim of this study was to explore the implications of this phenomenon on breeding. RNA sequencing coupled with methylation sequencing were used to scrutinize and compare gene expression profiles and methylation alterations in pollen and seeds during anther opening and closing, along with cold exposure.Genes enriched within Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were examined to identify gene clusters susceptible to temperature-related methylation changes in both pollen and seeds.Four pollen treatment models, namely normal control, "pollen protected from low temperatures," "pollen from just-opened anther," and "pollen from close-blocked anther," were used to produce corresponding seeds via artificial pollination. Subsequently, qRT-PCR was used to validate modifications in the expression patterns of marker genes in pollinated seeds under diverse treatment scenarios. Genes exhibiting significant differences in expression between anthers and normal tissues, along with gene regions linked to methylation variations attributed to low-temperature-treated pollen and seeds, were identified through transcriptomic analysis. Convergence was observed in three signaling pathways: oxidative phosphorylation (ko00190), plant hormone signal transduction (Ko04075), and zeatin biosynthesis (ko00908). Notably, gene clusters prone to temperature-induced methylation changes, such as NADH-ubiquinone oxidoreductase chain 5, plasma membrane ATPase 4, cytochrome c oxidase subunit 2, cis-zeatin O-glucosyltransferase, ABSCISIC ACID-INSENSITIVE 5-like protein 4, and indole-3-acetic acid-amido synthetase (IAAS), were identified. Evaluation using various pollen pollination models revealed altered expression patterns of five dormancy-regulating marker genes: IAAS, sucrose synthase (SUS), gibberellin 2-oxidase (GA2ox), ABA INSENSITIVE 2 (ABI2), and auxin-repressed protein (ARP), in seeds pollinated with pollen from close-blocked anthers, cold-protected pollen, and pollen from freshly opened anthers. The close-blocked anther treatment led to significantly upregulated expression of IAAS, SUS, GA2ox, and ABI2, whereas ARP expression decreased markedly, indicating a propensity towards prolonged seed dormancy. Conversely, in the low-temperature-protected anther model, SUS, ARP, GA2ox, and IAAS exhibited reduced expression levels, whereas the expression of ABI2 was upregulated, overall facilitating seed germination.